Development of soil nitrogen mapping system using apparent soil electrical conductivity sensor for paddy field - Mohd Husin, Ezrin; Wayayok, Aimrun; Mohd Soom, Mohd Amin; Bejo, Siti Khairunniza (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The emerging technology in agricultural research has changed the scenario for crop management. The precision farming concept is emphasized in parallel with the essential technology used in agriculture. The tools such as variables rate technology (VRT) or variable rate application (VRA) seems like compulsory for decision making purpose. Thus, this study was carried out to develop a rapid mapping system as a new tool for N-fertilizer application based on soil electrical conductivity data. The result from this study has proven the merit of the developed system in terms of its performance and its reliability. The total nitrogen map produced via this system was shown to be reliable for use in the site specific application for best management practices. The variability map produced from this system is slightly similar as a kriging map produced via ArcGIS. The findings of this study show that applying nutrients at optimal rates and at the right place with the assistance of technology is feasible to achieve high yield and high efficiency of nutrient use by the crop. The use of this mapping system as a basis of measuring the soil nutrient variability proved to be a good technique for the farmers to better manage their paddy fields.